Effects of core strength training on the technical skill performance of striking combat sport players: a systematic review - Zhang, Shuai; Huang, Wanyu; Soh, Kim Geok; Luo, Shengyao; Li, Long; Wang, Xinzhi (PeerJ Inc., 2025)
Research purpose. This review investigated the effects of core strength training on the competitive performance of players participating in striking combat sports. By analyzing karate, taekwondo, boxing, Chinese martial arts, and Muay Thai, the study examined the effects of core strength training on the number of kicks, striking force, and impact speed of players. The aim of this study was to provide a theoretical basis for training methods in striking combat sports and to explore the role of core strength in improving players' actual competitive performance. Methods. Data for this study were reported using the Preferred Reporting Project for Systematic Review and Meta-Analysis (PRISMA) guidelines. On November 1, 2023, a full search was conducted on SCOPUS, PubMed, Web of Science, EBSCO, CNKI (only core academic journals were included in the search, specifically those listed in recognized Chinese journal evaluation systems such as the Beijing University Core Journals or CSSCI, thereby excluding non-academic or low-tier publications.) and Google Scholar (via EBSCOhost) searching engine. PICOS determined the inclusion criteria: (1) Combat sports player; (2) core strength training; (3) the enhancement intervention was compared with the control group or other exercise groups, and a single-group test was conducted; (4) test at least one technical skill performance; (5) non-randomised research trials and randomised controlled designs. Only eight of the 826 studies met all inclusion criteria and were included in the systematic review. Results. In karate, wheel kick scores were significantly increased after core strength training; in taekwondo training groups, the number of kicks in 30 seconds was increased considerably; in boxing, 10-second and 20-second sandbag strikes and performance in 1 minute were significantly increased, and backhand punch strikes were enhanced; in martial arts, the striking power and relative striking power of straight punches and whip kicks were increased considerably; and in Muay Thai, jabs were made possible by both static and dynamic training; the knee strike and other manoeuvres had significant increases in striking power and impact speed. Overall, core strength training positively affected the frequency of kicks, striking power, and impact speed in all striking combat sports. Conclusion. The number of kicks, striking force, and impact speed in karate, taekwondo, boxing, Chinese martial arts, and Muay Thai have all improved, with particularly notable improvements in roundhouse kicks, straight punches, and whip kicks. core strength training has enhanced players' strength and physical stability, improving movement control and explosive power. Therefore, incorporating core strength training into striking combat sports training can comprehensively improve players' practical performance and physical fitness levels.